Tinjauan Pustaka : Kebiasaan Merokok dan Paparan Ultraviolet Sebagai Faktor Risiko Katarak Senilis - Ghaitsa Lulua; Himayani, Rani; Septiani, Linda; Berawi, Khairunnisa (Medula, 2025)
Cataract ranks second as the most common visual impairment and first as a cause of blindness, as the lens hardens and causes a decrease in sharp vision. Based on age, cataracts are divided into several types: congenital cataract, juvenile cataract and senile cataract. Senile cataract is a cataract that often occurs in older people. The classification of senile cataracts is based on the progression of the cataract's opacity, namely, incipient, immature, mature, and hypermature. Some of the risk factors for senile cataracts include a history of diabetes mellitus, family history, smoking, and exposure to ultraviolet light. Smokers have a higher risk of developing senile cataracts than non-smokers. Ingredients in cigarettes such as cyanate, nicotine and tar can cause changes and denaturation of proteins in the lens of the eye. Meanwhile, sunlight absorbed by the eye produces free radicals and affects the tissues in the lens of the eye, triggering oxidative reactions, causing changes in amino acid reactions and leading to senile cataracts.